Makna Budaya Topa Ma Ta Auba pada Masyarakat Desa Lasi, Kecamatan Kuanfatu, Kabupaten Timor Tengah Selatan - Manek, Agnes Odiyanti (Retorika: Jurnal Pembelajaran Bahasa dan Sastra Indonesia, 2021)
Top ma ta auba is one of the traditions and customs of the people of Lasi Village, Kuanfatu Subdistrict, South Central Timor District" to traditionally welcome visitors (the Government). Topa ma ta auba is the expression or narration of customary language which is delivered or spoken orally and reciprocates. The theory used is the theory of Hermeneutics as proposed by Palmer (2003:9) that hermeneutics is the study of understanding, especially understanding of the text. The sources of data in this study are the people of Lasi Village, especially traditional leaders and community leaders who know the customs in the area. Methods and techniques of data collection in research through are: 1). Direct observation; 2). Interview, 3). Record Techniques, 4). Note-taking technique. Data analysis of Tonis Topa mata auba, refers to the steps: 1). Tonis Topa ma ta auba transcribed from oral form into written form, 2). The transcription of the data into Indonesian, 3). Analyzing the data and determining the meaning in the data tonic topa mata auba, 5). Make a conclusion. data on the discussion of tonis topa mata auba in the Lasi Village community contains: (1). The meaning of the application; (2). Meaning of Politeness; (3). The meaning of humility; (4). Meaning of obedience; (5). The Meaning of Togetherness; and (6). The meaning of thank you.